2004
DOI: 10.1149/1.1669010
|View full text |Cite
|
Sign up to set email alerts
|

The Possibility of Carbonyl Fluoride as a New CVD Chamber Cleaning Gas

Abstract: Carbonyl fluoride false(COF2false) has been investigated as an alternative gas for plasma-enhanced chemical vapor deposition (PECVD) chamber cleaning in order to reduce greenhouse gases emitted from the cleaning process in semiconductor manufacturing. The cleaning performance of COF2 and the environmental impact of its exhaust gases were evaluated using an experimental plasma tool. The results indicated that the cleaning performance of COF2 was equivalent to that of conventional C2F6. Furthermore, it w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…Carbonyl fluoride, F 2 CO, has been recently suggested as a chamber-cleaning agent to replace the conventional perfluoroethane (Freon 116), C 2 F 6 , in plasma-enhanced chemical vapor deposition (PECVD), specially because of its reduced global warming potential (GWP), suggested, at most, to be the same as CO 2 . 1 The GWP estimation has been made on the basis that F 2 CO molecules react very quickly with water to produce CO 2 and HF. 1 Meanwhile Dibble et al 2 have studied the rate of formation of carbonyl fluoride at stratospheric altitudes and concluded that it is closely related to the rate of disappearance of CF 3 O.…”
Section: Introductionmentioning
confidence: 99%
“…Carbonyl fluoride, F 2 CO, has been recently suggested as a chamber-cleaning agent to replace the conventional perfluoroethane (Freon 116), C 2 F 6 , in plasma-enhanced chemical vapor deposition (PECVD), specially because of its reduced global warming potential (GWP), suggested, at most, to be the same as CO 2 . 1 The GWP estimation has been made on the basis that F 2 CO molecules react very quickly with water to produce CO 2 and HF. 1 Meanwhile Dibble et al 2 have studied the rate of formation of carbonyl fluoride at stratospheric altitudes and concluded that it is closely related to the rate of disappearance of CF 3 O.…”
Section: Introductionmentioning
confidence: 99%
“…C 2 H 2 F 2 , C 2 OF 2 , and CF 3 I are among the nonperfluorocarbons whose CF n radicals can be of great use for applications, and have thus been proposed as replacement gases. 1,2 In line with this we have carried out the first steps towards creating a cross section data set for this possibly industrially relevant species. In addition, from a physical and chemical point of view, the 1,1-difluoroethylene ͑1 , 1-C 2 H 2 F 2 ͒ molecules we study here are of interest since they have the peculiar intramolecular forces, molecular structure, and scattering dynamics of F-containing molecules supposedly lying midway between the pure hydrocarbon C 2 H 4 and the pure perfluorocarbon C 2 F 4 .…”
Section: Introductionmentioning
confidence: 99%
“…5 In this paper, we studied the interplay between the tetrel bond and hydrogen bond in the complexes composed of one F 2 XO (X = C and Si) and two HCN molecules. Carbonyl fluoride (F 2 CO), a chamber-cleaning agent, can replace the traditional perfluorocarbons used in the plasma semiconductor industry [33], and has some effects on the photochemistry of the Earth's upper atmosphere [34]. Hence, this study can provide some important information for the interactions between both interstellar molecules.…”
Section: Introductionmentioning
confidence: 99%